An overview of the air pollution trend in Klang Valley, Malaysia - Abdullah, Ahmad Makmom; Abu Samah, Mohd Armi; Tham, Yee Jun (2012)
The recent air pollution trend, as well as the factors that contribute to the air quality, were reviewed in the Klang Valley since it has undergone rapid development over the years. The overall quality of air in the Klang Valley was moderate for 66% of the days throughout the year of 2009 while only 5% of the days were classified at the unhealthy level. Shah Alam and Kuala Lumpur were among the cities that recorded the highest number of unhealthy days from 2001-2009. Furthermore, places around the Klang Valley suffered from quite severe acidified rain, which indicates that heavy air pollution is still occurringin areas around the Lang Valley. Factors like urbanization, industry, motor vehicles and forest fires remain the main contributors to the deterioration of air quality in the Klang Valley. Hence, a more sustainable policy has to be introduced by the government in order to tackle the air pollution issue.